Da'i Da'wah Methods in Developing Youth Religious Activities in Tangru Village, Malua District, Enrekang Regency - Rendi Rendi; Muhammad Qadaruddin; Nidaul Islam (Institut Agama Islam Negeri Parepare, 2021)
This study aims to find out what methods a preacher uses in developing religious activities and to find out what religious activities are carried out in Tangru Village, Malua District, Enrekang Regency. This study uses field research (Field Research) in collecting data about the methods used by da'i in developing religious activities in Tangru Village, Malua District, Enrekang Regency and library research (Library Search) in collecting data on da'wah methods. The data from this study were obtained from primary and secondary data, with data collection and processing techniques used, namely observation, interviews, and documentation. There are two theories used in this research, namely the theory of religious awareness and the theory of behavior. The results showed that not all da'wah methods were used by a Da'i in Tangru Village, Malua District, Enrekang Regency, only a few methods were used such as bil-Hikmah, bil-Lisan, and bil-Qalam da'wah methods. As for some religious activities carried out in Tangru Village, namely routine studies every Friday night and Tahsin learning. As well as being able to develop religious activities by showing good examples to teenagers, maintaining trust with the congregation and forming new study groups that have been fostered by Ustadz